The role of α′-martensite on the variation of compressive residual stress in a gradient nanostructured austenitic stainless steel - Yinsheng He; Hongyu Zhou; Wei Liu; Fangmiao Duan; Keesam Shin; Yuchen Zhao; Wenyue Zheng (Materials & Design, 2024)
The strain-induced martensitic transformation (α′-martensite) and residual stress (RS) introduction in the gradient nanostructured (GNS) austenitic stainless steel have been extensively reported in the last three decades, however, their correlation is still unclear. Here, the XRD, EBSD, ECCI and TEM were used to study the RS distribution and martensite behaviors in a GNS SS304 fabricated by ultrasonic surface nanocrystallization modification. We found the non-linear relationship between the magnitude of RS and the fraction of α′-martensite due to the role of α′-martensite in the development of type II intergranular RS. The maximum compressive RS of about 1,244 MPa was obtained as the γ-austenite and α′-martensite phases were each at approximately 50 %. Otherwise, the RS would decrease with the second phase fraction. The developed maximum compressive RS arises from the α′-martensite that formed directly from the γ-austenite. By contrast, the RS from other deformation structures, i.e., α′-martensite produced by γ → ε → α′, ε-martensite, nanotwin and dislocations, is relatively low. The current study classified the correlation of RS and the role of martensite for the first time, which may inspire new approaches for improving the fatigue properties of materials by controlling the phase fraction.